Decreased Bone Mineral Density with Off-Label Use of Tenofovir in Children and Adolescents Infected with Human Immunodeficiency Virus - Purdy, Julia B.; Gafni, Rachel I.; Reynolds, James C.; Zeichner, Steven; Hazra, Rohan (The Journal of pediatrics, 2008)
5 of 6 children infected with human immunodeficiency virus (HIV) receiving Tenofovir disoproxil fumarate (TDF) experienced absolute decreases in bone mineral density (BMD). 2 pre-pubertal subjects experienced >6% BMD decreases. 1 subject was the smallest child and experienced a 27% decrease, necessitating withdrawal of TDF. Subsequently, her BMD recovered. Monitoring of children infected with HIV who require treatment with TDF is warranted.